Diagnosis and management of mitochondrial disease: a consensus statement from the Mitochondrial Medicine Society - Parikh, Sumit (Genet Med, 2014)
PURPOSE: The purpose of this statement is to review the literature regarding mitochondrial disease and to provide recommendations for optimal diagnosis and treatment. This statement is intended for physicians who are engaged in diagnosing and treating these patients. METHODS: The Writing Group members were appointed by the Mitochondrial Medicine Society. The panel included members with expertise in several different areas. The panel members utilized a comprehensive review of the literature, surveys, and the Delphi method to reach consensus. We anticipate that this statement will need to be updated as the field continues to evolve. RESULTS: Consensus-based recommendations are provided for the diagnosis and treatment of mitochondrial disease. CONCLUSION: The Delphi process enabled the formation of consensus-based recommendations. We hope that these recommendations will help standardize the evaluation, diagnosis, and care of patients with suspected or demonstrated mitochondrial disease.